The effect of tensile strength and surface roughness by varying oxygen level in 3D printer chamber - Ramli, Faiz Redza; Sudin, Mohd Nizam; Alkahari, Mohd Rizal; Che Mat, Muhammad Arifuddin; Herawan, Safarudin Ghazali (Malaysian Tribology Society, 2022)
The part produced by the fused filament fabrication (FFF) 3D printer in terms of surface roughness, tensile strength, and dimensional accuracy depends mainly on the printing parameters and the environmental printing conditions. In this paper, nitrogen gas had been allowed to flow inside the 3D printer chamber to maintain an inert environment and to remove the rate of concentration oxygen inside the chamber. This paper is devoted to studying the influence of layer thickness and surface roughness on the mechanical properties of 3D-printed parts. Tensile and surface roughness tests were performed on samples of three different layer thicknesses (0.1mm, 0.2mm, and 0.3mm) using an Acrylonitrile Butadiene Styrene (ABS) in (FFF) 3D printing method. Therefore, the results explain the oxygen ambient is 10.295 (MPa) at the 0.1mm layer thickness for the tensile test, which is weaker than nitrogen ambient of 11.767 (MPa). The scanning electron microscope (SEM) observed a strong bonding with microstructure (fewer deficiencies and voids) for 0% oxygen, compared to 10% and 20% with the large void area.